SYNTHESIS OF QUINOLINE HETEROCYCLIC COMPOUNDS ANILINE USING MICROWAVE-ASSISTED METHODS - Zaman Abdalhussein Ibadi Alaridhee1, Nada Hasan2, Muhand Dohan Abid3 (Chelonian Research Foundation, 2023)
The synthesis of bioactive heterocyclic compounds has received considerable interest in the realm of medicinal chemistry owing to their wide range of biological activity and prospective uses in therapy. Microwave-assisted methodologies have developed as very effective instruments in the field of organic synthesis, facilitating expeditious and proficient alterations. The objective of this study is to investigate the use of microwave-assisted methodologies for the synthesis of bioactive heterocyclic compounds, with particular emphasis on the utilization of starting materials generated from natural sources. The usage of natural beginning materials has several benefits, including sustainability, accessibility, and the prospect of uncovering new molecules possessing distinctive biological features. The present study aims to elucidate the fundamental concepts behind microwave-assisted synthesis, while emphasizing current progress in this field. Furthermore, this review will exemplify the synthesis of bioactive heterocyclic compounds derived from natural starting materials. Moreover, this paper will examine the biological properties and possible practical uses of these substances, with a particular focus on the importance of microwave-assisted synthesis in the field of pharmaceutical research and advancement. Keywords: Bioactive heterocyclic compounds; microwave-assisted methodology; natural compounds; biological properties